PENGARUH ROLLING PEJABAT TERHADAP KUALITAS PELAYANAN PUBLIK (Suatu Studi Di Kantor Badan Kepegawaian dan Diklat Kabupaten Minahasa Selatan) - Mirah, Fatly; Rompas, Wilson Yappy; Tampi, Gustaf Budi (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT : Rolling is an incarnation or manifestation of the dynamics of organizations that serve as one way to achieve organizational goals and implemented to reduce the tedium of the job, increase knowledge, skills and increase the motivation and morale, in addition to placing the appropriate officials with expertise in the field of duty each. Problems to be answered in this research is how Rolling officials can affect the quality of public services in the scope of government staffing minahasa south. This study uses quantitative methods. This study aims to measure the relationship Rolling Minahasa district officials in the south with indicators of work experience, knowledge and skills and employees. This research was conducted by taking 5 samples at several SKPD with sample set of Â 20 respondents. Gathering date using questionnaires and interviews aided engineering. Date analysis using linear regression analysis and correlation of product moment. Management of data analysis using manual calculation formulas based on statistical analysis of linear regression and correlation product moment. Based on the analysis of the data showed: (1) correlation coefficient Rolling Minahasa officials in the southern district of the quality of public services is positive in the amount of 0.239 scale. (2) The correlation coefficient Rolling officials on the quality of public services delivery regency minahasa south is 0.306 while the coefficient of determination is 0.093 . Â results of these studies concluded that the influence of officials Rolling positive and significant impact on the quality of public services in the district minahasa south. Keywords: influence, rolling, quality, public service